Prevalence of Ethanol Use Among Pregnant Women in Southwestern Uganda - English, Lacey; Mugyenyi, Godfrey R.; Ngonzi, Joseph; Kiwanuka, Gertrude; Nightingale, Ira; Koren, Gideon; MacLeod, Stuart; Grunau, Brian E.; Wiens, Matthew O. (Women health journal, 2016)
The prevalence of ethanol use in many Sub-Saharan African countries is high and reported to be increasing among women. Some areas of Sub-Saharan African, such as regions of South Africa, have high rates of fetal alcohol spectrum disorder (FASD), but few data exist for other countries. The potential social and economic consequences of alcohol-exposed pregnancies are significant. The objective of this study was to determine the prevalence and predictors of ethanol use among women delivering at a regional hospital in Southwestern Uganda.
Keywords: Pregnancy; Alcohol; Fetal alcohol spectrum disorder; Sub-Saharan Africa